Pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) melalui Fasilitasi Pihak Eksternal dan Potensi Internal (Studi Kasus pada Usaha "Bonassacollection" di Kelurahan Tlogopatut, Kecamatan Gresik, Kabupaten Gresik) - Zalzabilah, Fadilah (Jurnal Bisnis Indonesia, 2024)
Development of Micro, Small and Medium Enterprises (MSMEs) Through Facilitation of ExternalParties and Internal Potential (Case Study of the "Bonassacollection" Business in Tlogopatut Village,Gresik District, Gresik Regency). Internal development of the "Bonassacollection" business inincreasing its potential by using initial capital with its own savings, innovating its production results,expanding its marketing network, and completing its business facilities and infrastructure. Apart fromthat, facilitation from external parties, namely Bapedda and UKM Tlogopatut Village, has providedMSMEs access to coaching and training, product promotion activities, expanding product marketing,as well as providing facilities and infrastructure. However, some entrepreneurs are hampered bylimited human resources, lack of facilities and infrastructure and lack of access to product marketing.Keywords: UMKM; Potential Internal